2021
DOI: 10.3389/fnmol.2021.680018
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Manipulation of Wnt/β-Catenin Signaling Pathway in Human Neural Precursor Cells Alters Their Differentiation Potential and Neuronal Yield

Abstract: The canonical Wnt/β-catenin pathway is a master-regulator of cell fate during embryonic and adult neurogenesis and is therefore a major pharmacological target in basic and clinical research. Chemical manipulation of Wnt signaling during in vitro neuronal differentiation of stem cells can alter both the quantity and the quality of the derived neurons. Accordingly, the use of Wnt activators and blockers has become an integral part of differentiation protocols applied to stem cells in recent years. Here, we inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…Our control data are consistent with the existing body of literature showing a decrease in canonical WNT pathway signaling over the course of neural induction ( Heeg-Truesdell and LaBonne, 2006 ; Huang et al, 2016 ; Telias and Ben-Yosef, 2021 ). Canonical WNT signaling promotes stem cell proliferation and inhibition of progenitor apoptosis ( Dravid et al, 2005 ; Davidson et al, 2007 ; Lee et al, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our control data are consistent with the existing body of literature showing a decrease in canonical WNT pathway signaling over the course of neural induction ( Heeg-Truesdell and LaBonne, 2006 ; Huang et al, 2016 ; Telias and Ben-Yosef, 2021 ). Canonical WNT signaling promotes stem cell proliferation and inhibition of progenitor apoptosis ( Dravid et al, 2005 ; Davidson et al, 2007 ; Lee et al, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
“…Because Wnt signaling plays a critical role in ISC self-renewal and differentiation, we next used the organoid culture system to determine whether HK2 expression was regulated by Wnt signaling. Treatment with CHIR99021, a Wnt agonist, 18 increased mRNA expression of HK2 and AXIN2 , a well-known Wnt target gene ( Figure 1 E ). In contrast, treatment with the tankyrase inhibitor, XAV939, which antagonizes Wnt, 18 dose-dependently decreased HK2 and AXIN2 mRNA expression ( Figure 1 F ).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with CHIR99021, a Wnt agonist, 18 increased mRNA expression of HK2 and AXIN2 , a well-known Wnt target gene ( Figure 1 E ). In contrast, treatment with the tankyrase inhibitor, XAV939, which antagonizes Wnt, 18 dose-dependently decreased HK2 and AXIN2 mRNA expression ( Figure 1 F ). We next determined whether loss of APC could increase HK2 expression because APC mutation leads to hyperactivation of Wnt signaling.…”
Section: Resultsmentioning
confidence: 99%
“…As the activation of the transgenic 3'reg1:GFP reporter via Tcf7l1a depletion would predict Wnt signaling should also regulate the 3'reg1:GFP reporter expression within the heart, we manipulated Wnt signaling in 3'reg1:GFP embryos at the 20 somite (s) stage with treatments of BIO and XAV939 (XAV), which respectively activate and inhibit Wnt signaling [56]. The 20s stage was chosen because we previously found that modulation of Wnt signaling could specifically affect AC number slightly prior to this stage at ~16s [51,53].…”
Section: Wnt Signaling Promotes Nr2f1a Expression In Acsmentioning
confidence: 99%